Formation of the Stakeholders Account Model in Conditions of Sustainable Development - Karpenko, Lidiia M.; Koev, Stoyan Radev; Kashchena, Nataliia B.; Grushko, Victor; Khorosheniuk, Andrii; Грушко, Віктор Іванович (Allied Business Academies, 2019)
The world experience regarding the interpenetration of the concept of sustainable development and responsible investing and accounting models is analyzed. The drivers of the appearance of the newest accounting model are determined, taking into account the specifics of the information requests of stakeholders. The stages of transformation of key forms of traditional reporting taking into account social and environmental components are considered. The determinants and principal features of the stakeholders accounting model are investigated in order to increase the validity of investment decisions. As a result of formalization, the hypothesis that the reporting on the sustainable development of accountable investment companies constituents is more transparent than the reporting of traditional financial index companies is disproved, taking into account the sub-periods of the global financial crisis identified and the division of financial markets for developed and developing countries. This has made it possible to confirm that the disclosure of information on ESG criteria is insufficient for decision makers in the financial sector of the economy and, in turn, determine the importance of its standardization. © 2019 Allied Academies.
Keywords: account model; corporate social responsibility; information requests; investment; stakeholders